Lesson co-planning: Joint Efforts, Shared Success - Carreño Bolívar, Laura; Hernandez Ortiz, Luz Stella (GIST – Education and Learning Research Journal, 2018)
The present article reports the results of a qualitative research study conducted at a higher education institution in Bogotá Colombia. The study aimed at examining the lesson planning practices conducted by English language teachers at the proficiency program of the institution. The participants were a mix of the mentors in charge of each level and teachers who agreed on being part of the study. Data was collected through two online surveys and one semi-structured interview; three categories were obtained from the data analysis; they focus on the planning stages, the impact of co-planning on teachers´ performance and the role of resources for lesson planning. The findings suggest that lesson planning collaboration among teachers provides them with the opportunity of improving their practices, and helped participants identify professional strengths and weaknesses.